Surface self-cleaning polypropylene material and preparation method thereof
Through melt blending and hot pressing, low-surface energy particles are enriched on the surface of polypropylene materials, solving the problems of complex processes of existing superhydrophobic materials and easy surface structure failure, and achieving good hydrophobicity and self-cleaning properties of the materials.
Patent Information
- Application Number
- CN202411535972.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-18
AI Technical Summary
The existing superhydrophobic materials have complex processes and easy surface structure to be damaged, resulting in reduced hydrophobic performance. How to easily enrich low-surface energy particles on the surface of the material to build a micro-nano rough structure is a key issue.
Through melt blending and hot pressing, the surface fluorosilane-grafted nanosilia is blended with polypropylene, and the mutual attraction of the hot press pad is used to migrate and enrich the hydrophobic modifier to the surface, thereby Giving materials good surface self-cleaning properties.
The surface self-cleaning effect of polypropylene material is achieved, the hydrophobicity of the material is improved, the operation is simple, the process is easy to control, and the surface water contact angle is ≥120°.
Smart Images

Figure CN119463355A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a surface self-cleaning polypropylene material and a preparation method thereof. Background Art
[0002] Superhydrophobic materials are widely used in our lives, such as self-cleaning, anti-icing, oil-water separation, antibacterial, etc. There are many superhydrophobic phenomena in nature, such as lotus leaves that "come out of the mud without staining", water striders that "skate in the pond", compound eyes of flies, rice leaves, butterfly wings, etc. At present, there are mainly methods such as templates, phase separation, plasma etching, chemical vapor deposition, etc. to construct rough structures on the surface of materials, so that the surface presents a typical Cassie morphology and achieves superhydrophobicity. However, this series of methods generally have the disadvantages of complex processes and irreversible mechanical damage to the surface structure during long-term use, resulting in reduced hydrophobic properties. Using low surface energy particles such as fluorinated silanes to hydrophobically modify materials is an effective means. Fluorinated silanes have the dual characteristics of organic fluorine and organic silicon, which can make the modified substrate have excellent comprehensive properties such as hydrophobicity, antifouling, and self-cleaning. Fluorocarbon-based low surface energy precursors, such as fluorosilanes, are used to functionalize silica nanoparticles to obtain superhydrophobic surfaces, which has become a hot research field for the preparation of hydrophobic materials. How to easily enrich low surface energy particles on the surface of materials to construct micro-nano rough structures is the key to making the material surface hydrophobic.
[0003] One of the common methods of hydrophobic modification is to coat the substrate surface with a low surface energy substance by coating, but the operation is complicated, and the low surface energy substance is difficult to adhere and unstable. The method of combining the substrate with the hydrophobic modifier by blending also has the problem of low modifier utilization and high addition amount. Summary of the invention
[0004] The purpose of the present invention is to provide a polypropylene (PP) material with a surface self-cleaning effect and a preparation method thereof, which utilizes a simple melt blending and hot pressing method, with the help of the mutual attraction between the hot pressing pad and the modifier, to promote the migration and enrichment of the hydrophobic modifier from the inside of the composite material to the surface, thereby giving the PP material good surface self-cleaning performance.
[0005] To achieve the purpose of the invention, the scheme of the present invention is as follows:
[0006] A method for preparing a surface self-cleaning polypropylene material comprises the following steps:
[0007] (1) melt-blending PP, nano-silica (m-SiO2) grafted with fluorine-containing silane on the surface, and maleic anhydride grafted polypropylene (MAH-g-PP) to obtain a composite material;
[0008] (2) Covering the surface of the obtained composite material with a fluorine-containing backing plate, hot pressing at 160-190° C., allowing the surface of the composite material to contact the backing plate for at least 15 minutes, thereby obtaining a polypropylene material with a self-cleaning surface.
[0009] Furthermore, the fluorine-containing silane is selected from any one or more of perfluorohexyltrichlorosilane, nonafluorohexylmethyldichlorosilane, nonafluorohexyltrimethoxysilane, perfluorohexylethyltrichlorosilane, perfluorohexylethyltriethoxysilane, perfluorooctylethyltrichlorosilane, and perfluorooctyltriethoxysilane.
[0010] Furthermore, the PP is isotactic polypropylene.
[0011] Furthermore, the temperature of melt blending in step (1) is 160-200°C.
[0012] Furthermore, step (1) is performed by melt blending in an open-milling manner, and the open-milling time is 5 to 10 minutes.
[0013] Furthermore, the preparation method of the surface fluorine-containing silane-grafted nano-silicon dioxide (m-SiO2) comprises the following steps:
[0014] (a) dispersing nano-silicon dioxide in a mixed solution of ethanol and ammonia water;
[0015] (b) slowly dripping fluorinated silane into the dispersion obtained in (a), stirring and reacting for 3 to 5 hours;
[0016] (c) After the reaction is completed, the reaction solution is centrifuged to remove the lower precipitate, which is then washed with alcohol, and then centrifuged again to remove the lower precipitate after the alcohol washing;
[0017] (d) Repeat the centrifugation and alcohol washing process 1 to 3 times, and then dry in an oven at 50 to 80° C. for 12 to 36 hours to obtain the m-SiO 2 .
[0018] Furthermore, the fluorine-containing silane is one of perfluorohexyltrichlorosilane, nonafluorohexylmethyldichlorosilane, nonafluorohexyltrimethoxysilane, perfluorohexylethyltrichlorosilane, perfluorohexylethyltriethoxysilane, perfluorooctylethyltrichlorosilane, and perfluorooctyltriethoxysilane.
[0019] In the above preparation method, ammonia water is used as a catalyst, and after the fluorine-containing silane undergoes hydrolysis, condensation and other reactions, the hydrophobic groups are grafted onto the surface of the nano-silica particles, so that the hydroxyl groups on the surface of the nano-silica particles are reduced, thereby achieving the effect of hydrophobic modification.
[0020] Furthermore, the particle size of the nano-silicon dioxide is 20 to 100 nm.
[0021] Furthermore, the nano-silica is hydrophilic nano-silica.
[0022] Furthermore, the mass ratio of the fluorine-containing silane added in step (b) to the nano-silicon dioxide is (2.55-12.76):1.
[0023] Furthermore, the volume ratio of ammonia water to ethanol used to prepare the mixed solution in step (a) is 1:(9-12).
[0024] Furthermore, in the composite material, the mass fraction of PP is 70-95 parts, the mass fraction of m-SiO2 is 2-20 parts, and the mass fraction of MAH-g-PP is 1-5 parts.
[0025] Furthermore, the grafting rate of the MAH-g-PP is 0.6% to 1.2%.
[0026] Furthermore, an antioxidant is added in step (1), and the antioxidant can be antioxidant 1010. The antioxidant can improve the anti-aging performance of the composite material; the added amount of the antioxidant is 1% to 5% of the total mass of the composite material.
[0027] Furthermore, the content of fluorine-containing silane in the m-SiO2 is 20% to 60%.
[0028] Furthermore, step (2) includes two steps of hot pressing. The first step is hot pressing and leveling, and the material of the pad used is not limited, such as any one of polyethylene terephthalate film (PET), polytetrafluoroethylene sheet (PTFE), polyimide (FPI), and silicone plate; the second step is hot pressing migration, using a fluorine-containing pad.
[0029] Furthermore, during the first step of hot pressing and leveling, the pressing plate temperature is 150-200° C., the hot pressing time is 15-30 minutes, and after the hot pressing is completed, cold pressing (maintaining pressure) is continued for 5-10 minutes.
[0030] Furthermore, during the second step of m-SiO2 migration, the pressing plate temperature is 160-190°C, the hot pressing time is 15-30 minutes, and cold pressing is continued for 5-10 minutes after the hot pressing is completed.
[0031] Furthermore, the material of the fluorine-containing backing plate in step (2) is selected from any one of polytetrafluoroethylene, fluorinated polyimide, polyperfluoroethylene propylene, and polyvinylidene fluoride.
[0032] Furthermore, the hot pressing pressure used in step (2) is 8 to 20 MPa.
[0033] The invention also provides a surface self-cleaning polypropylene material, which is obtained by adopting the above preparation method.
[0034] Beneficial effects:
[0035] (1) The present invention adds m-SiO2 to the PP substrate and utilizes the attraction of the substrate to m-SiO2 during plate pressing to enrich the m-SiO2 on the PP surface. The low surface energy of m-SiO2 itself and the micro-nano structure of the nanoparticles themselves form a rough structure on the PP surface, forming a papillary structure similar to the surface of a lotus leaf, thereby greatly improving the hydrophobicity of PP.
[0036] (2) The present invention adopts a melt blending method to prepare a hydrophobic PP material, which is simple to operate and easy to control the process.
[0037] (3) The surface water contact angle of the self-cleaning hydrophobic PP obtained by the present invention is ≥120°, and has good self-cleaning hydrophobic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0039] Figure 1 It is a schematic diagram of the preparation process of m-SiO2 of the present invention;
[0040] Figure 2 1 is a diagram of the migration mechanism of m-SiO2 in a polypropylene substrate of the present invention, wherein (I) represents before hot pressing surface modification; (II) represents during hot pressing surface modification; (III) represents after hot pressing surface modification;
[0041] Figure 3 Surface SEM images of the composite materials obtained in Example 5 and Comparative Example 24 of the present invention, wherein (a) is the composite material obtained in Comparative Example 24; (b) is the composite material obtained in Example 5;
[0042] Figure 4 The contact angle test results of the present invention are: (a) the contact angle test results of the materials obtained by using different substrate press plates and different m-SiO2 addition amounts; (b) the contact angle test results of the materials obtained by hot pressing the composite material with 10% m-SiO2 content covering the PTFE plate for different times;
[0043] Figure 5 These are the test results of the self-cleaning performance of the present invention. (a1-a2) are the effect diagrams of the PP material (unmodified) obtained in Comparative Example 24 before and after self-cleaning; (b1-b2) are the effect diagrams of the PP composite material obtained in Example 5 before and after self-cleaning. DETAILED DESCRIPTION
[0044] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0045] The steps of the m-SiO2 preparation method used in the following examples are as follows:
[0046] (a) Dissolve hydrophilic silica (1 g) in ethanol (100 ml) and ammonia water (10 ml) in a three-necked flask and stir for 30 min to disperse the silica evenly;
[0047] (b) After stirring evenly, slowly drop 0.01 mol of perfluorooctyltriethoxysilane into (1) into a three-necked flask, keep the rotation speed at 800 r / min, and continue stirring for 4 h;
[0048] (c) After the reaction is completed, the reaction solution is placed in a centrifuge tube and centrifuged at 8000 r / min for 20 min. The upper clear liquid is removed and poured out. The lower precipitate is washed with 30 ml of anhydrous ethanol. The centrifugation and washing process is repeated three times, and then dried in an oven at 70°C for 24 h to obtain m-SiO2.
[0049] Example 1
[0050] (1) m-SiO2, commercial PP, MAH-g-PP, and antioxidant 1010 are melt-blended on an open mill, wherein the mass ratio of m-SiO2, PP, and MAH-g-PP is 0.2:9.3:0.5, the amount of antioxidant 1010 is the same as that of MAH-g-PP, the melt-blending temperature is 180°C, and the open mill time is 5 minutes to obtain a composite material;
[0051] (2) The obtained composite material is pressed and flattened on a flat plate press, using a PET film as a backing plate, the pressing plate temperature is 190° C., the hot pressing time is 20 min, and the cold pressing time is 8 min;
[0052] (3) The PET film backing plate was replaced by a PTFE plate and hot pressing was performed again, with the platen temperature being 190°C, the hot pressing time being 20 min, the hot pressing pressure being set to 10 MPa, and the cold pressing time being 8 min;
[0053] (4) Obtain the composite material and conduct contact angle test and self-cleaning performance test.
[0054] Embodiments 2 to 7
[0055] The preparation steps of Examples 2 to 7 are the same as those of Example 1, except that in step (1), the mass fractions of m-SiO2, PP, and MAH-g-PP are: 0:9.5:0.5, 0.5:9:0.5, 0.8:8.7:0.5, 1:8.5:0.5, 1.5:8:0.5,
[0061] 2:7.5:0.5.
[0062] Comparative Examples 1 to 7
[0063] Comparative Examples 1 to 7 correspond to the mass fraction ratios of m-SiO2, PP, and MAH-g-PP in Examples 1 to 7, respectively. In step (3), a silicone gasket is used to replace the PTFE plate, and the remaining steps are the same as in Example 1.
[0064] Comparative Examples 8 to 14
[0065] Comparative Examples 8 to 14 correspond to the mass fraction ratios of m-SiO2, PP, and MAH-g-PP in Examples 1 to 7, respectively, and the step of replacing the PET film backing plate with a PTFE plate and then performing hot pressing is eliminated, that is, step (3) is eliminated, and the remaining steps are the same as in Example 1.
[0066] Comparative Examples 15 to 23
[0067] The preparation process is the same as that of Example 5, except that:
[0068] In step (3), the hot pressing time is 11min, 12min, 13min, 14min, 15min, 30min, 40min, 50min and 60min respectively, and the cold pressing time is 8min.
[0069] Comparative Example 24
[0070] The PP pellets were milled at 180°C and then pressed with a PET film at 190°C to prepare samples. The wettability of the obtained PP surface was characterized and its contact angle was measured.
[0071] Performance Testing
[0072] Hydrophobic performance test
[0073] The contact angle test was performed on the composite materials of different substrates and press plates obtained in each embodiment and comparative example using a contact angle measuring instrument. The test results are shown in the attached figure. Figure 4As shown, the contact angle of the sample prepared by PTFE plate pressing plate is significantly improved compared with that prepared by silicone gasket and PET film pressing plate, and the preheating time also has a certain influence on the contact angle. When the hot pressing time reaches 20 minutes, the contact angle reaches stability. This is because both PTFE and m-SiO2 contain a large amount of fluorine elements, which can attract each other, so that m-SiO2 can migrate and enrich on the surface of polypropylene to form a surface with low surface energy, and the micro-nano structure of m-SiO2 itself can also construct a rough structure on the surface of polypropylene. These two together improve the hydrophobicity of the polypropylene surface. When the preheating time is 20 minutes, m-SiO2 completely migrates and the contact angle reaches stability.
[0074] Self-cleaning effect test
[0075] Use dust as a pollutant to verify the self-cleaning performance of the obtained material surface: place dust on the sample surface, tilt the sample 15°-20° from the horizontal direction, then use a dropper to drip water onto the material surface with the pollutant, and observe the cleanliness of the sample surface. It can be seen that the surface self-cleaning ability of the material is significantly improved by adopting the modification method of the present application.
[0076] Finally, it should be noted that the specific embodiments used in this specification are only preferred embodiments of the present invention. It should be noted that for those skilled in the art, the specific embodiments and application scope may be changed during implementation according to the concept of the present invention. Therefore, the contents recorded in this specification should not be understood as limiting the present invention.
Claims
1. A method for preparing a surface self-cleaning polypropylene material, characterized in that: The steps include: (1) melt-blending polypropylene, nano-silica grafted with fluorine-containing silane on the surface, and maleic anhydride grafted polypropylene to obtain a composite material; (2) Covering the surface of the obtained composite material with a fluorine-containing backing plate, hot pressing at 160-190° C., allowing the surface of the composite material to contact the backing plate for at least 15 minutes, thereby obtaining a polypropylene material with a self-cleaning surface.
2. The preparation method according to claim 1, characterized in that: The fluorine-containing silane is selected from any one or more of perfluorohexyltrichlorosilane, nonafluorohexylmethyldichlorosilane, nonafluorohexyltrimethoxysilane, perfluorohexylethyltrichlorosilane, perfluorohexylethyltriethoxysilane, perfluorooctylethyltrichlorosilane, and perfluorooctyltriethoxysilane.
3. The preparation method according to claim 1 or 2, characterized in that: The preparation method of the nano-silica with fluorine-containing silane grafted on the surface comprises the following steps: (a) dispersing nano-silicon dioxide in a mixed solution of ethanol and ammonia water; (b) slowly dripping fluorinated silane into the dispersion obtained in (a), stirring and reacting for 3 to 5 hours; (c) After the reaction is completed, the reaction solution is centrifuged to remove the lower precipitate, which is then washed with alcohol, and then centrifuged again to remove the lower precipitate after the alcohol washing; (d) Repeat the centrifugation and alcohol washing process 1 to 3 times, and then dry in an oven at 50 to 80° C. for 12 to 36 hours to obtain nano-silica with fluorine-containing silane grafted on the surface.
4. The preparation method according to claim 1, characterized in that: In the composite material, the mass fraction of polypropylene is 70-95 parts, the mass fraction of nano silicon dioxide grafted with fluorine-containing silane on the surface is 2-20 parts, the mass fraction of antioxidant is 1-5 parts, and the mass fraction of maleic anhydride grafted polypropylene is 1-5 parts.
5. The preparation method according to claim 1, characterized in that: The grafting rate of the maleic anhydride grafted polypropylene is 0.6% to 1.2%.
6. The preparation method according to claim 1, characterized in that: The content of fluorine-containing silane in the nano silicon dioxide with fluorine-containing silane grafted on the surface is 20% to 60%.
7. The preparation method according to claim 1, characterized in that: Step (2) comprises two steps of hot pressing. The first step is hot pressing and flattening, and the pad used is selected from polyethylene terephthalate film; the second step is hot pressing and surface modification, and any one of a fluorine-containing material pad, polytetrafluoroethylene sheet, and silicone sheet is used.
8. The preparation method according to claim 1, characterized in that: The material of the fluorine-containing pad in step (2) is selected from any one of polytetrafluoroethylene, fluorinated polyimide, polyperfluoroethylene propylene, and polyvinylidene fluoride.
9. The preparation method according to claim 1, characterized in that: In step (1), an antioxidant is also added, which can improve the anti-aging performance of the composite material.
10. A surface self-cleaning polypropylene material, characterized in that: The preparation method according to any one of claims 1 to 9 is used to obtain the
Citation Information
Cited By
Modified polypropylene for pipette tip and preparation method thereof
CN122277814A